Kepemimpinan Musyrif dalam Meningkatkan Mutu Pembelajaran Al-Qur’an - Ariyanto, Ariyanto; Subando, Joko (Lembaga Yasin AlSys, 2026)
Musyrif leadership, exercised by dormitory mentors who accompany students in the pesantren environment, plays a strategic role in directing Qur'anic learning processes, as their intensive daily interactions with santri contribute to the formation of discipline, motivation, and consistency in memorization. This article aims to conceptually analyze the characteristics and dimensions of musyrif leadership, evaluate its contribution to improving the quality of Qur'anic learning, and develop a conceptual model that depicts the interrelationships among leadership attitudes, santri motivation, dormitory discipline, and memorization outcomes. This study is based on a literature review that draws on leadership theories in Islamic education, management of learning processes, and empirical research on tahfizh education published in leading national journals. The review shows that musyrif leadership is complex and encompasses spiritual exemplarity, moral conduct, disciplinary supervision, and instructional functions within the tahfizh process; the integration of these four aspects is aligned with transformational, moral, and instructional leadership theories that emphasize behavioral change, value internalization, and learning optimization. Previous empirical findings indicate that musyrif with strong competencies can enhance perseverance in muroja’ah, the quality of memorization, self-regulation, and the formation of Qur'anic character among santri. Therefore, strengthening musyrif leadership capacity, enhancing leadership training, and implementing character-oriented learning management constitute strategic measures for sustainably improving the quality of tahfizh education, both at the level of dormitory management practices and in the development of conceptual leadership frameworks in Islamic education.